1998
DOI: 10.1161/01.hyp.32.5.945
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Oscillation Regulates Human Mesangial Cell Growth and Collagen Synthesis

Abstract: Abstract-Experimental renal disease models establish glomerular hypertension as a crucial determinant in glomerulosclerosis progression and demonstrate that glomerular capillary pressure reduction delays sclerosis development. An oscillating pressure (OP) chamber was constructed as an in vitro model to study human mesangial cells. Cell cultures were grown under atmospheric pressure (AP) and a controlled OP corresponding to intraglomerular capillary pressure. We show that OP significantly decreases mesangial ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 26 publications
3
15
0
Order By: Relevance
“…In this system under basal culture conditions, total collagen production by mesangial cells was unaffected by high pressure; however, collagen accumulation increased when cells were exposed to both high pressure and a high glucose concentration, as might occur in a diabetic patient with hypertension [9]. This finding is similar to that of Riser et al [10] who reported that the combination of a high glucose concentration and cyclic stretch increased TGF-␤ secretion and collagen accumulation by mesangial cells.…”
Section: Mechanism By Which Glomerular Hypertension Promotes Injurysupporting
confidence: 86%
“…In this system under basal culture conditions, total collagen production by mesangial cells was unaffected by high pressure; however, collagen accumulation increased when cells were exposed to both high pressure and a high glucose concentration, as might occur in a diabetic patient with hypertension [9]. This finding is similar to that of Riser et al [10] who reported that the combination of a high glucose concentration and cyclic stretch increased TGF-␤ secretion and collagen accumulation by mesangial cells.…”
Section: Mechanism By Which Glomerular Hypertension Promotes Injurysupporting
confidence: 86%
“…Rat mesangial cells were established as previously described [52,53]. Human monocytic THP-1 as well as human breast adenocarcinoma MCF-7 (Michigan Cancer Foundation-7) cells were obtained from the ATCC.…”
Section: Methodsmentioning
confidence: 99%
“…Rat mesangial cells (MCs) were established and characterized as described previously (15,16) and were grown in RPMI 1640 medium supplemented with 10% fetal calf serum, 2 mM L-glutamine, 100 g/ml streptomycin, and 100 units/ml penicillin at 37°C in humidified 5% CO 2 in air. HK-2 cells were maintained as described previously (17).…”
Section: Cells and Culture Conditionsmentioning
confidence: 99%